Jesus, the Apostle and High Priest of Our Confession. Audience-Oriented Criticism of Heb 3:1-6 - Blajer, Piotr (The Biblical Annals, 2021)
Hebrews 3:1-6 is one of the most intriguing passages of the letter. It catches the attention of who reads or hears the letter for several reasons: one of which is the way the author presents Jesus Christ. It establishes a comparison between Moses and Christ in order to demonstrate Christ’s superiority as the high priest and apostle. It is the only passage in the New Testament where Jesus is presented as an apostle. The reader-oriented research points out to the way the author addresses the audience of his letter and how he manages to catch their attention and present their present status. Those who accept Christ’s mission as the apostle are sanctified and can be considered the house of God governed by Christ.